REGULATION AND FUNCTION OF THE FGF23/KLOTHO ENDOCRINE PATHWAYS - Martin, Aline (2012)
Calcium (Ca(2+)) and phosphate (PO(4)(3−)) homeostasis are coordinated by systemic and local factors that regulate intestinal absorption, influx and efflux from bone, and kidney excretion and reabsorption of these ions through a complex hormonal network. Traditionally, the parathyroid hormone (PTH)/vitamin D axis provided the conceptual framework to understand mineral metabolism. PTH secreted by the parathyroid gland in response to hypocalcemia functions to maintain serum Ca(2+) levels by increasing Ca(2+) reabsorption and 1,25-dihydroxyvitamin D [1,25(OH)(2)D] production by the kidney, enhancing Ca(2+) and PO(4)(3−) intestinal absorption and increasing Ca(2+) and PO(4)(3−) efflux from bone, while maintaining neutral phosphate balance through phosphaturic effects. FGF23 is a recently discovered hormone, predominately produced by osteoblasts/osteocytes, whose major functions are to inhibit renal tubular phosphate reabsorption and suppress circulating 1,25(OH)(2)D levels by decreasing Cyp27b1-mediated formation and stimulating Cyp24-mediated catabolism of 1,25(OH)(2)D. FGF23 participates in a new bone/kidney axis that protects the organism from excess vitamin D and coordinates renal PO(4)(3−) handling with bone mineralization/turnover. Abnormalities of FGF23 production underlie many inherited and acquired disorders of phosphate homeostasis. This review discusses the known and emerging functions of FGF23, its regulation in response to systemic and local signals, as well as the implications of FGF23 in different pathological and physiological contexts.